The Renaissance as Failure and New Beginning: Vladimir Bibikhin’s Interpretation of European History in The New Renaissance - Evlampiev, Igor (Stasis, 2015)
In The New Renaissance, V. Bibikhin defines “a renaissance” in general terms as an attempt to overcome a historical crisis and to provide a new impulse for the development of both people and society. In this sense, there have been many renaissances, but the main one—the Italian Renaissance—was a unique event during which humankind attempted to unleash its creative essence in all its fullness. At the same time, the Renaissance was an attempt to reestablish the true teachings of Jesus Christ and to overcome the false doctrine of the Christian church, which separated people from God through the idea of sin. The 15th–16th century Renaissance was suppressed by the church and this occasioned the continuing crisis and decline of European civilization; which could only be saved by a new renaissance.